DeFi and the metaverse: Legal and regulatory challenges of decentralisation of financial services - REMOLINA LEON, Nydia (Institutional Knowledge at Singapore Management University, 2024)
Decentralized Finance, known as DeFi (Decentralized Finance), refers to the use of blockchain and digital assets or crypto-assets for the provision of financial services. Through DeFi applications, services such as loans, insurance, crypto-asset exchanges, among others, are offered, and are structured based on crypto-assets and technologically decentralized applications. This paper will discuss the concept of DeFi and how it challenges the traditional market infrastructures of the financial sector, demystifying the idea of absolute decentralization, generally mentioned in the crypto-asset arena. Subsequently, the paper will analyze the opportunities and challenges of DeFi for consumers, financial institutions, new competitors and financial regulators. Among the opportunities, it will present how DeFi could contribute to financial inclusion, to the automation of certain financial products, and how it is a key factor for the development of metaverses. As part of the challenges, the paper will analyze the problems of money laundering and terrorist financing in these markets, financial consumer protection, corporate governance issues, the lack of transparency of these products, cybersecurity risks and systemic risk. Finally, the paper will address some early regulatory responses that policymakers have proposed in response to some of these challenges in different jurisdictions.